2018
DOI: 10.30880/jtmb.2018.10.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Consumer Perception and its Impact on Purchase Intention for Residential Property Market

Abstract: The objective of this study is to investigate the effects of customer perceived value on customer purchase intention in the residential property market in Malaysia. The research proposes extension of Seth et al., 1991 model for property market by including relational aspect of the value as an added new parameter. Explanatory research design approach is used in this study with primary data collection through questionnaire survey of 172 respondents using convenience sampling method. The collected data and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Many studies have shown that perceived value is an important antecedent variable of behavior intention. A study on the Malaysian housing market, it was found that functional value, social value, relationship value, situational value and cognitive value have significant positive effects on purchase intention [ 61 ]. In the study of revisiting tourist destinations, when a tourist with a high perceived value in a tourist destinations tend to revisit or actively recommend behaviors in the future [ 62 ].…”
Section: Hypothesis Development and Conceptual Modelmentioning
confidence: 99%
“…Many studies have shown that perceived value is an important antecedent variable of behavior intention. A study on the Malaysian housing market, it was found that functional value, social value, relationship value, situational value and cognitive value have significant positive effects on purchase intention [ 61 ]. In the study of revisiting tourist destinations, when a tourist with a high perceived value in a tourist destinations tend to revisit or actively recommend behaviors in the future [ 62 ].…”
Section: Hypothesis Development and Conceptual Modelmentioning
confidence: 99%